Dynamics of a vertical cavity quantum cascade phonon laser structure - Maryam, W.; Akimov, Andrey V.; Campion, R.P.; Kent, Anthony (Nature Publishing Group, 2013)
Driven primarily by scientific curiosity, but also by the potential applications of intense sources of coherent sound, researchers have targeted the phonon laser (saser) since the invention of the optical laser over 50 years ago. Here we fabricate a vertical cavity structure designed to operate as a saser oscillator device at a frequency of 325 GHz. It is based on a semiconductor superlattice gain medium, inside a multimode cavity between two acoustic Bragg reflectors. We measure the acoustic output of the device as a function of time after applying electrical pumping. The emission builds in intensity reaching a steady state on a timescale of order 0.1 μs. We show that the results are consistent with a model of the dynamics of a saser cavity exactly analogous to the models used for describing laser dynamics. We also obtain estimates for the gain coefficient, steady-state acoustic power output and efficiency of the device.